Conditions and calibration to obtain comparable grey values between different clinical cone beam computed tomography scanners - England, Gregory M (Dentomaxillofac Radiol, 2017)
OBJECTIVES: The objective of the present study was to examine the grey value parameters and their magnitudes produced by CBCT and whether they are influenced by different scanners with various scanning conditions. METHODS: An ATOM Max dental and diagnostic artificial head was scanned by two CBCT scanners (Planmeca and iCAT). Under full field of view with normal dose and ultralow-dose (ULD) conditions, the Planmeca scanner was examined for three scanning resolutions (200, 400, and 600 micron voxel sizes) and the iCAT scanner was tested for four scanning resolutions (200, 250, 300 and 400 micron voxel sizes). After 9 weeks, the artificial head was scanned again by the Planmeca scanner with the same scanning conditions. In addition, two hydroxyapatite phantoms (1220 and 1540 mg cm(−3)) were adhered on the artificial head and scanned using normal and ULD scanning conditions of 400 micron voxel size with both scanners. The grey value histogram of each region, which is proportional to the bone mineral density (BMD) histogram, was utilized to determine grey value distribution parameters and compare scanners (ANOVA, p < 0.05). RESULTS: The different scanning conditions and the bilateral locations of the artificial head did not have significant effects on measurements of the grey value parameters (p > 0.436) with excellent repeatability. However, the iCAT scanner produced significantly different grey values from the Planmeca scanner (p < 0.001). CONCLUSIONS: CBCT can assess BMD, while calibration of absolute measures is necessary to obtain comparable values between different scanners that are currently used to assess oral bone quantity and quality.